2017
DOI: 10.1111/cge.13126
|View full text |Cite
|
Sign up to set email alerts
|

Recessive mutations in NDUFA2 cause mitochondrial leukoencephalopathy

Abstract: Deficiencies of mitochondrial respiratory chain complex I frequently result in leukoencephalopathy in young patients, and different mutations in the genes encoding its subunits are still being uncovered. We report 2 patients with cystic leukoencephalopathy and complex I deficiency with recessive mutations in NDUFA2, an accessory subunit of complex I. The first patient was initially diagnosed with a primary systemic carnitine deficiency associated with a homozygous variant in SLC22A5, but also exhibited develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
2
10
2
Order By: Relevance
“…Consistent with the MRI findings of our case, the two children reported by Perrier et al showed confluent T2‐hyperintense and cystic changes of supratentorial white matter without involvement of basal ganglia . In contrast to the cases by Perrier et al, our case had an involvement of the corpus callosum, a tigroid‐like pattern of the deep white matter, and restriction of the DWI‐signal.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Consistent with the MRI findings of our case, the two children reported by Perrier et al showed confluent T2‐hyperintense and cystic changes of supratentorial white matter without involvement of basal ganglia . In contrast to the cases by Perrier et al, our case had an involvement of the corpus callosum, a tigroid‐like pattern of the deep white matter, and restriction of the DWI‐signal.…”
Section: Discussionsupporting
confidence: 91%
“…Although MRI images were not available, the pattern of neuroimaging abnormalities of the first reported patient with NDUFA2 defect appears to be different compared to the present case and the two other cases reported by Perrier et al This first case with NDUFA2 defect indeed showed an early‐onset of demyelination of cortico‐spinal tracts and subacute necrotizing encephalomyelopathy, as observed in Leigh syndrome . Consistent with the MRI findings of our case, the two children reported by Perrier et al showed confluent T2‐hyperintense and cystic changes of supratentorial white matter without involvement of basal ganglia . In contrast to the cases by Perrier et al, our case had an involvement of the corpus callosum, a tigroid‐like pattern of the deep white matter, and restriction of the DWI‐signal.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations